How can interactive multimedia direct instruction model improve student cognitive learning outcomes? - Malik, Adam; Wandira, Ayu; Kuntadi, Dedi; Nugraha, Andi Rohendi (Momentum: Physics Education Journal, 2022)
This study aims to determine the implementation of the direct instruction model based on interactive multimedia and the lecture model as well as the differences in the improvement of students' cognitive learning outcomes after the two models are applied to the material of effort and energy. The method in this study uses a quasi-experimental method, with a Noneequivalent Control Group design. The research sample consisted of two classes, namely class X-IPA 1 as the experimental class and class X-IPA 2 as the control class, each consisting of 20 students. Data on the implementation of learning were obtain-ed through observation sheets and students' cognitive learning outcomes were obtained through multiple-choice tests. The data analysis technique used the calculation of the observation sheet, N-gain, and t-test. The results showed that the average percentage of all meetings on the implementation of learning in the experimental class was 82.78% with very good interpretation and 71.85% in the control class with good interpretation. The increase in students' cognitive learning outcomes in the experimental class was 0.58 in the medium category and in the control class was 0.29 in the low category. The results of hypothesis testing using an independent sample t-test showed the value of tcount (3.56) > ttable (2.02). The results showed that there were differences in the cognitive learning outcomes of students who studied with an interactive multimedia-based direct instruction model and lecture model. Thus, the interactive multimedia-based direct instruction model is better in improving students' cognitive learning outcomes in the matter of effort and energy. This study could be implemented in schools with proper or non-proper laboratory facilities for supporting the learning of physics.